A Morphological and Anatomical Study of Ferns on the Campus of the Kwame Nkrumah University of Science and Technology (KNUST), Kumasi, Ghana - Addo-Fordjour, Patrick (2011)
A thesis submitted to the Department of Theoretical and Applied Biology, College of Science in partial fulfilment of the requirements for Master of Science degree.